2022
DOI: 10.1186/s12884-022-04922-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of management approaches for hyperemesis gravidarum and nausea and vomiting of pregnancy: a retrospective questionnaire analysis

Abstract: Background Hyperemesis gravidarum is the most severe form of nausea and vomiting of pregnancy, or morning sickness. 2% of pregnancies in the United States are affected by hyperemesis gravidarum. The condition is characterized by severe vomiting in pregnant people, especially during the first trimester, often leading to hypovolemia and weight loss. The standard of care for hyperemesis and nausea and vomiting of pregnancy is commonly ineffective. We hypothesize that based on patient experience; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(41 reference statements)
0
2
0
2
Order By: Relevance
“…A sample of 786 women in the United States who experienced treatment of HG participated in an online survey. 15 Sixty percent of the women were formally diagnosed with HG. Of these participants, 57% reported taking 3 or more medications to try to alleviate their symptoms.…”
Section: Treatment Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…A sample of 786 women in the United States who experienced treatment of HG participated in an online survey. 15 Sixty percent of the women were formally diagnosed with HG. Of these participants, 57% reported taking 3 or more medications to try to alleviate their symptoms.…”
Section: Treatment Experiencesmentioning
confidence: 99%
“…The trials included antiemetic pharmacological interventions and nonpharmacological interventions, such as acupuncture. A sample of 786 women in the United States who experienced treatment of HG participated in an online survey 15. Sixty percent of the women were formally diagnosed with HG.…”
Section: Introductionmentioning
confidence: 99%
“…Ein einheitliches Vorgehen wurde bisher nicht definiert. Wie eine jüngste Untersuchung aus den USA (n = 1002) ergab, nahmen 22,4% der Schwangeren mit HG 3, 15,3% 4 und 19,4% ≥5 Antiemetika 71 . Statt dieser Polypragmasie in der Therapie der HG ist ein am Schweregrad der Symptome orientiertes Stufenkonzept erforderlich 11 13 61 beginnend mit der niedrigsten Stufe wie z.…”
Section: Therapieunclassified
“…Ondansetron: in den USA stieg zwischen 2001 und 2014 die Anwendungsrate von Ondansetron von 1% auf 13–25% (500000–1000000 Anwendungen auf 4 Millionen Schwangerschaften) deutlich an 107 . Nach einer Untersuchung von Mares et al 2022 71 ist in den USA Ondansetron das am häufigsten eingesetzte Antiemetikum bei HG. Nach einer randomisierten Doppelblindstudie soll Ondansetron zur Behandlung des persistierenden Erbrechens (nicht aber der Übelkeit) in der Schwangerschaft effektiver sein als Metoclopramid 108 .…”
Section: -Ht3-antagonisten (Setrone)unclassified
“…Studies showed a possible connection between hormone levels during pregnancy, known as human chorionic gonadotropin (hCG). This hormone tends to peak around the 10th week of pregnancy (5). Other factors that could potentially play a role in HG include psychological aspects, digestive system issues, Helicobacter pylori infection, thyroid problems, and liver complications.…”
Section: Introductionmentioning
confidence: 99%